"Building Today for the Womanhood of Tomorrow": Businessmen, Boosters, and the YWCA, 1890-1930 - Pedersen, Diana (Urban History Review / Revue d'histoire urbaine, 1987)
Women's organizations played an active part in the Progressive movement for the reform of North American cities in the early twentieth century. Women reformers could and did cooperate with men but had their own distinct perception of the city and their own definition of urban reform. Lacking capital and political power, however, women were forced to depend on the support of male reformers and had to address themselves to the men's concerns. This study examines the relationship between the Young Women's Christian Association and Canadian businessmen as it was manifested in a number of successful fund-raising campaigns for YWCA buildings in Canadian cities between 1890 and 1930. YWCA women "sold" their building to the business community as a sound investment and an asset that would reflect well on the reputations of enterprising business leaders and a modern progressive community.